Gender equality and paid parental leave in Australia: A decade of giant leaps or baby steps?. (September 2021) - Baird, Marian; Hamilton, Myra; Constantin, Andreea
The year 2020 marks the 10th anniversary of the Australian Paid Parental Leave Act 2010. Using Baird's orientations typology and Brighouse and Wright's equality framework, with evidence from the Workplace Agreements Database and the Workplace Gender Equality Agency, this article assesses changes in policy, bargaining and company provisions over the decade. We find that policy changes may enable more fathers and partners to take leave, although the period is short and barriers to uptake exist. In bargaining and company policy, we find modest growth in the proportion of agreements with paid primary and paid secondary carer leave provisions, but no movement in the duration of the leaves, with secondary carer leave much shorter. We conclude that although these changes suggest growing attention to improving women's working conditions and fathers' access to parental leave, short secondary carer leaves set normative standards of fathers as 'supporters' rather than recognising substantive involvement in care. Consequently, the changes do not promote gender-egalitarian sharing of parental leave. While the introduction of the government scheme was a 'giant leap', the 10 years since have seen modest 'baby steps' towards greater gender equality in the availability and potential use of paid parental leave.